Applied machine learning for the risk-stratification and clinical decision support of hospitalised patients with dengue in Vietnam - Ming, DK; Hernandez, B; Sangkaew, S; Vuong, NL; Lam, PK; Nguyet, NM; Tam, DTH; Trung, DT; Tien, NTH; Tuan, NM; Chau, NVV; Tam, CT; et al. (Public Library of Science, 2022)
Background Identifying patients at risk of dengue shock syndrome (DSS) is vital for effective healthcare delivery. This can be challenging in endemic settings because of high caseloads and limited resources. Machine learning models trained using clinical data could support decision-making in this context.